Thermomechanical analysis of a toughened thermosetting system. - Zarrelli, M.; Skordos, Alexandros A.; Partridge, Ivana K. (Springer Science Business Media, 2008)
The experimental results of viscoelastic mechanical tests, at five different levels of conversion, are reported for a thermoset composite matrix system toughened with an appropriate percentage of a thermoplastic polymer. The results from static tests are used to construct the master curves at a specific degree of cure, while the shift factors are compared with the corresponding values from dynamic experiments in order to assess the validity of the time-temperature superposition for each conversion. Neat resin plates were cured accurately, according to the full kinetics model for a dynamic and isothermal temperature regime; the conversion gradient in the plane and across the thickness of the plates was assessed by a thermal analysis of samples taken from different locations before extracting the samples from them. The viscoelastic behaviour of the resin matrix showed a sensible difference in the relaxation time spectrum upon conversion according to the provisional trend of mobility theory; a higher conversion induced a horizontal shift of the principal relaxation time for each level of conversion, which could be related very well to the glass transition at the same conversion. Good results were also obtained for the ultimate modulus of the resin at a temperature just before the onset of the co-curing phase for partially cured samples
Keywords: mechanical properties; viscoelasticity; time-temperature superposition; conversion; thermoset